Clinical use of aclidinium in patients with COPD - Reid, Debra J (Dove Medical Press, 2014)
Chronic obstructive pulmonary disease (COPD) is the sixth-leading cause of death in the US. The Global initiative for Chronic Obstructive Lung Disease (GOLD) guidelines provide evidence-based recommendations for the clinical management of chronic COPD. Long-acting inhaled bronchodilators continue to be the mainstay of current management. Aclidinium bromide (Tudorza™ Pressair™) joins tiotropium as a long-acting inhaled antimuscarinic bronchodilator approved by the US Food and Drug Administration for the maintenance treatment of COPD. Early studies demonstrated aclidinium’s significant bronchodilatory effects supporting once-daily dosing; however, two Phase III studies, Aclidinium Clinical Trial Assessing Efficacy and Safety in Moderate to Severe COPD Patients (ACCLAIM/COPD) I and ACCLAIM/COPD II, in which patients were randomized to receive aclidinium 200 μg daily, failed to achieve the minimal clinically important difference in improvement of trough forced expiratory volume in 1 second (FEV(1)), suggesting the need for higher doses or more frequent dosing. Additional studies – Aclidinium to Treat Airway Obstruction in COPD Patients (ATTAIN) and Aclidinium in Chronic Obstructive Respiratory Disease (ACCORD) I – were undertaken to compare 200 and 400 μg twice-daily dosing. The mean improvements from baseline in trough FEV(1) in the 400 μg groups were +129 mL over 24 weeks and +124 mL over 12 weeks in ATTAIN and ACCORD I, respectively. Aclidinium also had beneficial effects on health-related quality of life and other endpoints, such as rescue medication use and rates of exacerbations. Aclidinium bromide inhalation powder is generally well tolerated in patients with COPD, with headache, cough, diarrhea, and rhinosinusitis among the most commonly reported adverse events. Cardiovascular side effects were rarely reported. Patient satisfaction studies found that patients using the aclidinium delivery device had fewer errors affecting drug delivery than those using the tiotropium device and, overall, the aclidinium device was preferred to the tiotropium device. In conclusion, aclidinium bromide is approved for use in the US at a dose of 400 μg twice daily and is a promising alternative to tiotropium.